Disordered eating among university athletes in Singapore - Chan, Tin Wing (2019)
With an increase in competitiveness in sports, the risk of disordered eating among athletes are at a rising stake. Traditionally, females athletes are deemed to be more prone in having disordered eating than males athletes. However, with a change in expectation and idealising a certain body image due to various reasons like culture norms, male athletes are at a rising risk of having disordered eating. Many past researches focus on the aesthetics sports and weight class sports but few researches show awareness on ball sports. In addition, with information easily available on social media platforms, athletes may be misled by the unvalidated information. The purpose of this research is to uncover the prevalence of the attitude and behaviour of disorder eating among university ball sports athletes. A 18 item questionnaire is given to each participant. Thematic analysis and correlation test were used to analyse the data to identify the common themes and the relations of the reasons behind the participant’s engagement in disordered eating. The three main themes are for aesthetic, performance and health purposes.